Peningkatan Mutu Sdm Pokdarwis Melalui Sosialisasi Sport Massage Untuk Pertolongan Pertama Dalam Kecelakaan Di Desa Wisata Belitar Seberang - Azizatul Banat; Roni Syaputra; Dwinki Marta Pura; Oppa Chorindo; Randy Ardiansyah (Universitas Dehasen Bengkulu, 2023)
Belitar Seberang Village, Sindang Kelingi District, Rejang Lebong Regency, Bengkulu Province is one of the tourist villages that received a tourism village award in 2022 from the Ministry of Tourism and Creative Economy. Belitar Seberang Tourism Village is also a fostered village of Dehasen University Bengkulu, and in the context of community service carried out by a team of lecturers from the Teaching and Education Faculty which is divided into several service groups including one of which is the lecturer service group which carries the title